The Urgency Of Improving Social Piety In The Perspective Of Tarbawi Hadith (Hermeneutic Analysis About Community Life) - Khamim, Khamim (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2018)
The issues of moral degradation are increasingly widespread. Developments have more or less given their influence on human personality, including Muslims. Tracing back, many hadith have told us about the importance of cultivating superior morals and personality. This article will examine the importance of fostering social piety in the perspective of tarbawi hadith. Hermeneutic analysis using a qualitative approach to literature study becomes a tool for a more comprehensive new synthesis. From the analysis, it can be concluded that moral education is indeed often alluded to in various hadiths of the Prophet. This is not surprising anymore considering the main mission of the Prophet Muhammad sent by Allah SWT to this world is to perfect morals. Moral education certainly comes from strong faith in humans. Strong faith will bring about noble character, which is then called individual piety. Individual piety can be seen from ritual piety and certainly will lead to social piety. Community life is not as easy as imagined, because it requires good interpersonal sensitivity and quality. That is why the Prophet often reminded Muslims to get used to social piety, starting from the ethics of visiting and being able to receive guests, or also the elegant ways of living. Of course social piety can start from small things such as answering greetings, visiting sick people, arranging bodies, fulfilling invitations, or also praying for our brothers who sneeze. Good social piety will certainly strengthen ukhuwah Islamiyah. All of this is expected to create a superior Islamic civilization. Therefore, in tarbawi hadith, social piety is indeed important to be cultivated in daily life.